Topolins: Current Research Status and Applications - Subbaraj, Arvind Kumar (International Journal of Bio-resource and Stress Management, 2023)
Institute of Natural Resources, Massey University, Private Bag 11-222, Palmerston North (4442), New Zealand Topolins are hydroxylated analogues of 6-benzylaminopurine (BAP). They belong to a group of cytokinins with an aromatic side chain, in contrast to the isoprenoid group which contain an aliphatic side chain. Though topolins have been identified in diverse plant species, knowledge on their biosynthesis, signal transduction and metabolism is limited. Recent research advances in the isoprenoid group can therefore provide a template to direct further research on topolins. In spite of their high biological activity, applications of topolins to date have focused primarily on their use as an alternative source of cytokinin in micropropagation. The review starts with a primer on the history, nomenclature and chemical structure of topolins. A list of topolins identified in different plant species is provided to substantiate their widespread occurrence. A brief description of recent findings on the biosynthesis and metabolism of the isoprenoid group is offered to compare and contrast existing information on topolins. Determination of the biological activity of the stereoisomers of topolins is described as influenced by their chemical structure and signal perception. An account of the existing and plausible applications of topolins in yield accumulation, alleviating dormancy and abiotic stress management is provided. Finally, the review expresses confidence that topolins will play a significant role in the emerging scenario that cytokinins could hold the key to the next green revolution.